A Comparative Study on the Importance of Milk and Milk Products as a Complete Food - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana; Manoharmayum, Dolpriya Devi (Integrated Journal for Research in Arts and Humanities, 2022)
Milk is a commonly consumed soft drink essential to many people's overall diet as it provides all crucial foods and micronutrients. Milk is considered valuable because it is synthesized before adolescence and adulthood. However, its relatively high soaked fat content raises the question of whether it can negatively affect the cardiovascular system. This study evaluates the latest publications on dairy products and human well-being, as described in epidemiological, academic, and biochemical evidence. For example, the effects of milk (especially skim milk) on body weight appear irrefutable, and the most famous studies show that the use of dairy products does not increase the incidence of cardiovascular problems or certain tumors. The study was conducted using a questionnaire and targeted two types of dairy products: packaged and unpackaged. The evidence is inconclusive, but some studies suggest that milk and its by-products may help some populations. Future studies will help clarify the role of milk and dairy products in human well-being, but their use in a proper diet should be considered without explicit contraindication fragments.